PEMANFAATAN PENGOLAHAN CITRA DAN KLASIFIKASI K-NEAREST NEIGHBOR PADA CITRA TELUR AYAM - Mochamad Aryo Aji Kurniawan, (2020)
Eggs can be categorized into two in the hatching process i.e. Fertil eggs (fertile) and infertile eggs (Gabuk). The examination of Fertility (fertility) of eggs can be done by pressing the egg itself commonly called candling, by bringing the egg closer to the light source to penetrate the egg shell. The identification process is often done by manual process by the egg breeder so that it will require more clarity in doing so and increase the likelihood of misidentifying it. Based on the purpose of this research is done to identify fertil chicken eggs and infertile chicken eggs by extracting the color characteristics of the egg using the Hue saturation Values (HSV) method and using classification using K-Nearst Neighbor (KNN) algorithm to help the digital image processing process. With the K-NN method obtained accuracy of 100% on test K = 1